(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Epithelial tissues represent the fundamental building blocks of the human body’s organs and systems. Proficiency in the histological understanding of epithelial tissues is indispensable for medical students. This article investigates a diverse array of strategies and methodologies to optimize the pedagogy of epithelial tissue histology in medical universities. By incorporating innovative pedagogical techniques, harnessing cutting-edge technologies, and fostering active learning, medical educators can elevate students’ comprehension and retention of epithelial tissue histology. This paper provides an exhaustive examination of the materials, methods, and outcomes associated with these strategies, underlining the imperative of continual enhancement in medical histology education.